2007
DOI: 10.1063/1.2799997
|View full text |Cite
|
Sign up to set email alerts
|

Biatomic substrates for bulk-molecule interfaces: The PtCo-oxygen interface

Abstract: We develop an ab initio procedure for materials participating in electron transfer reactions, to consider biatomic backgrounds (e.g., substrates, catalysts, electrodes), thus the precise effects of the continuum and long-range interactions as well as the effects of the discrete and local nature of the chemistry can be combined to study molecules under such biatomic backgrounds. We test this new procedure by studying the reactivity of molecular oxygen on bimetallic clusters of platinum and cobalt. The reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The cc-pVTZ is a full electron basis set that uses a 7s,6p,4d,2f,1g basis for zinc and 4s,3p,2d,1f for oxygen . These methods have been widely tested in several types of systems from molecular electronics to catalysis to biological systems , and confirmed to provide acceptable results when compared to available experimental results; some of these methods yield results close to chemical accuracy …”
Section: Methodsmentioning
confidence: 99%
“…The cc-pVTZ is a full electron basis set that uses a 7s,6p,4d,2f,1g basis for zinc and 4s,3p,2d,1f for oxygen . These methods have been widely tested in several types of systems from molecular electronics to catalysis to biological systems , and confirmed to provide acceptable results when compared to available experimental results; some of these methods yield results close to chemical accuracy …”
Section: Methodsmentioning
confidence: 99%
“…Here we are able to combine the continuous and discrete wave function in the same formalism . The transmission probability, T , and the total density of states, D , of the molecular junction are calculated as follows: ,, T false( E , V false) = normalT normalr normala normalc normale ( normalΓ 1 false( E , V false) G normalM false( E , V false) normalΓ 2 false( E , V false) G normalM + false( E , V false) ) D false( E , V false) = normalT normalr normala normalc normale false( i [ G normalM false( E , V false) G normalM + false( E , V false) ] S false( V false) false) where Γ i = √−1(Σ i ( E , V )) – Σ i + ( E , V ) ( i , j = 1,2) describes the coupling between the contacts and the molecule, S ( V ) is the overlap matrix at each applied voltage, G M is the retarded Green function for the standalone molecule and G M + is its adjoint.…”
Section: Methodsmentioning
confidence: 99%
“…It has been showed that Stone–Wales (SW) defects yield changes in the electronic properties of graphene and affect the reactivity toward the adsorption of adsorbates. ,,, It is also known that the presence of vacancies in graphene nanoribbons modifies the electronic transport properties, affecting the conductance of these nanomaterials. ,, A study on multivacancies in carbon nanotubes has also revealed the existence of stability at magic numbers . Graphene-based complexes have been explored in energy conversion, electrical conduction, solubility, and composites formation. , …”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic activity of alloys is strongly dependent on the manner in which the atoms are arranged at the surface of the catalysts. [29][30][31] This arrangement of the atoms is inuenced by the ability of the atoms to migrate from the core of the particle to the surface layer (i.e., 'surface segregation'). The phenomenon of surface segregation has been shown by both theory and experiment to be of critical importance in the design and performance of new electrocatalysts.…”
Section: Basic Principles Underlying Metal Nanoparticleenhanced Electmentioning
confidence: 99%